Upacara Mulo Cucu Ayae Sebagai Ide Penciptaan Karya Batik Dua Dimensi - Nadia Plastika; Mega Kencana (VisArt: Jurnal Seni Rupa dan Design, 2025)
The Mulo Cucu Ayae ceremony is one of the traditions of the Kerinci community, especially in Sungai Liuk Hamlet, Pesisir Bukit District, Sungai Penuh City. The Mulo Cucu Ayae ceremony is a ceremony to inaugurate the marriage of the first daughter. The purpose is for the bride and groom to pray for blessings from traditional figures and ask for prayers for blessings and safety of life to God through custom so that the bride and groom are given easy sustenance and are given offspring. The basic theories used are form theory, function theory, color theory and aesthetic theory. Form theory is a special form because of the reciprocal relationship between symbolic values ​​and the visual form of the work. The method of creation is through the stages of exploration, direct observation, literature study, collection of photo and video documentation related to the Mulo Cucu Ayae ceremony. The form of this work is a two-dimensional wall decoration of seven works measuring 90 cm x 65 cm. Each work depicts the stages in the Mulo Cucu Ayae ceremony, from preparation to closing and is entitled: “Jamuan” and “Sumpah Sembah”